Pemikiran Ahmad Muhammad Mustain Nasoha tentang Hak Asasi Manusia (HAM), Kewarganegaraan dan Negara Hukum Demokratis: Suatu Analisis Teoritis - Halwa Ainun Tsaqifah; Siwi Adi Batullatifah; Chelsea Alya Mukhbita; Tiara Aurellia Khalisah Putri (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
This study discusses Ahmad Muhammad Mustain Nasoha’s perspective on Human Rights (HAM) and the Democratic Rule of Law, emphasizing the relationship between national law and Islamic law in ensuring human dignity and justice. Using a qualitative method and literature study approach, this research analyzes the interaction between citizenship, human rights, and democracy within Indonesia’s legal framework. The study reveals that both national and Islamic law aim to protect individual rights and maintain justice, though they differ in philosophical foundations and application. National law defines citizenship and human rights through constitutional and legal frameworks, while Islamic law bases them on divine principles emphasizing moral and social responsibility. The integration of these two legal systems is essential to realize a democratic state that upholds human values, social justice, and equality. The study concludes that harmonizing Islamic law with Indonesia’s national law strengthens the implementation of human rights and supports the development of a just and democratic legal state.